Produção e caracterização físico-química de quitosana extraída de isolados de cunninghamella sp. - Lopes, Jeane Cândida (Universidade Federal do Tocantins, 2017)
Commonly found in high humidity soils, the fungi of the Zygomycetes class, in particular the Cunninghamella elegans species, are widely studied and used in the biotechnology area, primarily by having larger amounts of chitin and chitosan in their cell walls. This study aimed to isolate and identify Cunninghamella sp. strains, evaluate the metabolic profile of the isolates in liquid medium YPD (Yeast extract, Peptone, Dextrose), and then quantify the production of biomass, chitin and chitosan by the strains. In the end, evaluated the quality of chitosan obtained by physicochemical tests. This study initially isolated 20 strains on growing areas soils in southern Tocantins, where, after macroscopic and microscopic identification and comparison with the reference strain C. elegans (CBMAI 0843), it was confirmed that it is related to the Cunninghamella gender strains. After evaluating the mycelial growth rate, which was considered fast, it was observed that the isolated UFT Ce09 and UFT Ce08 showed a higher growth rate. Then, the strains sporulation was evaluated, which resulted in all strains reaching the 106 spores.mL-1 concentration within 96 hours. The isolates UFT Ce09, UFT Ce14 and UFT Ce07 showed higher sporulation. The metabolic profile of the isolates in YPD medium submerged culture showed metabolic similarities with the reference strain. The YPD was considered optimal for biomass production, to promote efficient consumption and synthesis of organic compounds by microorganisms. The assessment of biomass production and yield of chitin and chitosan of nine isolates and reference strain showed that the isolated UFT Ce08 had the highest quantity of biomass, the isolated UFT Ce11 had the highest yield of chitin and the isolated UFT Ce09, even with the second lowest biomass, had the highest yield of chitosan. Seven strains showed higher chitosan compared to the reference strain. The fungal chitosan had a high degree of deacetylation, thus increased solubility, low molecular weight and infrared spectra similar to the commercial chitosan, parameters that make this chitosan interesting for various applications. The study considered the Cunninghamella fungi as a promising alternative source for the chitosan large scale extraction and commercialization.